2023
DOI: 10.1002/rse2.335
|View full text |Cite
|
Sign up to set email alerts
|

Capturing long‐tailed individual tree diversity using an airborne imaging and a multi‐temporal hierarchical model

Abstract: Measuring forest biodiversity using terrestrial surveys is expensive and can only capture common species abundance in large heterogeneous landscapes. In contrast, combining airborne imagery with computer vision can generate individual tree data at the scales of hundreds of thousands of trees. To train computer vision models, ground‐based species labels are combined with airborne reflectance data. Due to the difficulty of finding rare species in a large landscape, many classification models only include the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
(66 reference statements)
0
0
0
Order By: Relevance
“…Following tree detection, we classified each predicted crown as “Alive” or “Dead” based on the RGB data. Presented in [ 27 ], this Alive-Dead model is a 2 class resnet-50 deep learning neural network trained on hand-annotated images from across all NEON sites. During prediction, the location of each predicted crown was cropped and passed to the Alive-Dead model for labeling as Alive (0) or Dead (1) with a confidence score for each class.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Following tree detection, we classified each predicted crown as “Alive” or “Dead” based on the RGB data. Presented in [ 27 ], this Alive-Dead model is a 2 class resnet-50 deep learning neural network trained on hand-annotated images from across all NEON sites. During prediction, the location of each predicted crown was cropped and passed to the Alive-Dead model for labeling as Alive (0) or Dead (1) with a confidence score for each class.…”
Section: Methodsmentioning
confidence: 99%
“…To classify each predicted crown tree crown to species, we use the 1-m hyperspectral data and a multi-temporal hierarchical model. Ref [ 27 ] found that a hierarchical model outperforms a flat model by improving rare species accuracy. The hierarchical model organizes tree species into submodels, allowing each model to learn better features related to distinguishing similar classes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…‘Pine’, and were limited to less than 10 classes ( Persson et al, 2004 ; Heikkinen et al, 2010 ). The emergence of deep learning networks in computer vision, combined with greater data availability, led to a large number of publications combining deep learning with a variety of sensors and data acquisition platforms ( Fricker et al, 2019 ; Kattenborn et al, 2021 ; Mäyrä et al, 2021 ; Weinstein et al, 2023 ). A defining challenge of individual species classification is the fine-grained nature of the task, with subtle differences among co-occurring species, often within the same taxonomic genus.…”
Section: Introductionmentioning
confidence: 99%